Jaden Scott: capstone - Scott, Jaden, artist (Colorado State University. Libraries, 2023)
The artist's statement: Memories are invaluable to me. They are passed from person to person, generation to generation, friend to friend, and will outlive what they remember. Sharing these memories through storytelling, artifacts, hidden meanings, and manifested abstract ideas are the goals of my work. Being able to show a deeply personal experience from the inside and share it outwardly is at the root of my expression of memories. I create to hold onto family, friends, past and future versions of myself, and my own challenges I faced in small physical fragments. My work is a collection of personal souvenirs. My personal souvenirs are all rooted in narratives: being diagnosed with an incurable disease, past and future versions of myself, my background in dance, my exploration of gender, and, most prominently: my heritage. My grandparents were farmers and lived on a multi-acre farm, their work ethic and overall way of life heavily inspire my work and the narratives I tell. It is important for me to take these experiences and transform them into work, through which I take the time to reflect on them and myself during the process. In my metals practices, I focus on non-jewlery ways to adorn the body that add meaning to the work itself. The location at which something is placed on the body is very important to me as a way of describing the feeling inside and showing what that manifests from that outside. Examples of this include medical images of different areas of my abdomen and recreating them to be worn in their same locations on the outside or trying to describe the abstract feeling of love and memory and placing it over the heart. I focus on the body itself and how the forms and feelings inside the body can be depicted exteriorly. By creating work that dives into deeply personal stories, I am able to dissect the impacts certain events had on me and process them through my work. Taking multiple hours to go through the process of creating a piece allows me time to sit with the ideas and events, and come out the other side a little bit wiser. There is a lot of nuance in the choices I make during my process and I can spend hours detailing the entire story and reasoning in each piece I make. It is my goal to share my narratives, my love for the craft, and myself through my works.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing; jewelry